(untitled) (ARQUISUR Revista, 2015)
From the first decade of the twentieth century, urban growth of the city of Córdoba clearly begins to exceed the limits of the potential of development of the local territory. The new technologies enable development to meet the demands of population and economic growth experienced by the city. This process is accentuated since the 1940s, with the industrial development of the city and peripheral expansion over traditional core of foundational city and its first extensions (Nueva Córdoba and so–called "Barrios people"). The 60s consolidate these processes of peripheral extension. But from the 70s we are witnessing the emergence of the phenomenon of metropolization of Córdoba, with consequent disruptions of production processes of the urban and the emergence of new urban–territorial logics (decentralization, fragmentation, dispersion, diffusion, chosen segregation–forced segregation, large projects in "special areas", new connectivities), the characteristics, conditions and sustainability deficits show that the new modes of production of urban are sources of larger and more complex environmental problems in local-regional scale.